PENGARUH METODE KONVENSIONAL, GRUP INVESTIGATION DAN PROBLEM SOLVING, JENIS KELAMIN TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MAHASISWA PGSD UPY - Selly Rahmawati (Universitas PGRI Yogyakarta, 2015)
The aim of this research was to determine the effect of cooperative learning Group Investigation (GI) and problem solving (PS) methods, the sex against the critical thinking skills of students on civicslesson. This study used factorial design study. Location of the study conducted in PGSD UPY.Research was held in November. Subjects population in this study was Students PGSD UPY who takethe Civics course of the school year 2014. Subject sample is determined by using purposive sample byselecting three classes that have the same cognitive abilities. In this study, there are two variablesstudied were the independent variables (method of investigation group learning, problem solving andconventional), the dependent variable (critical thinking skills) and (sex). This study uses datacollection techniques such as observation and documentation. Data analysis techniques used in thisresearch is the technique of quantitative analysis using ANOVA.The results of this research is: (1)there is a difference between the critical thinking skills of students studying the group investigationmethods, problem solving and conventional. (2) there is a difference between the critical thinkingskills of students who have sex men and women. (3) there is no significant interaction between methodof the sex.